Scalable Manufacturing of Solderable and Stretchable Physiologic Sensing Systems. Issue 39 (24th August 2017) - Kim, Yun‐Soung; Lu, Jesse; Shih, Benjamin; Gharibans, Armen; Zou, Zhanan; Matsuno, Kristen; Aguilera, Roman; Han, Yoonjae; Meek, Ann; Xiao, Jianliang; Tolley, Michael T.; Coleman, Todd P.
Abstract: Methods for microfabrication of solderable and stretchable sensing systems (S4s) and a scaled production of adhesive‐integrated active S4s for health monitoring are presented. S4s' excellent solderability is achieved by the sputter‐deposited nickel‐vanadium and gold pad metal layers and copper interconnection. The donor substrate, which is modified with "PI islands" to become selectively adhesive for the S4s, allows the heterogeneous devices to be integrated with large‐area adhesives for packaging. The feasibility for S4‐based health monitoring is demonstrated by developing an S4 integrated with a strain gauge and an onboard optical indication circuit. Owing to S4s' compatibility with the standard printed circuit board assembly processes, a variety of commercially available surface mount chip components, such as the wafer level chip scale packages, chip resistors, and light‐emitting diodes, can be reflow‐soldered onto S4s without modifications, demonstrating the versatile and modular nature of S4s. Tegaderm‐integrated S4 respiration sensors are tested for robustness for cyclic deformation, maximum stretchability, durability, and biocompatibility for multiday wear time. The results of the tests and demonstration of the respiration sensing indicate that the adhesive‐integrated S4s can provide end users a way for unobtrusive health monitoring. Abstract : Heterogeneous soft adhesive electronics provides a means of noninvasive, unobtrusive health monitoring by synergizing the benefits of a stretchable circuit platform and small surface‐mount electronic components. The proposed manufacturing method utilizes four industry‐standard processes enabling a scaled production of soft adhesive electronics. A demonstration of respiratory monitoring implies the potential impact the soft adhesive electronics could have on healthcare.